Keanekaragaman Dioscorea spp dan habitatnya di Kabupaten Kudus, Jawa Tengah Diversity and habitat of Dioscorea spp in Kudus, Central Java - Fatma, Lania Yuchanitz; Jumari, J; Utami, Sri (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
Dioscorea spp (Yam) is one of the potential local food producers. It has advantage of high species diversity, containing high carbonhydrate and easy to grow. The aim of this research is to determine the variants of Dioscorea spp, examine the structure and composition of trees around Dioscorea spp habitat and determine the enviromental factors of Dioscorea spp habitat. The research was carried out in May-June 2017. The sampling technique was using exploration and quadratic method by plotting the trees into 5 squares (10 m x 10 m) with diameter of stem more than 10 cm. The name of each species, number of individuals and stem diameter measurement of each plot were recorded. The data of diversity Dioscorea spp and environmental factors were analyzed by sort of descruptive set and the trees was analyzed by vegetation analysis. The results showed that 4 species of Dioscorea spp. There are D. hispida, D. bulbifera, D. alata and D. esculenta. D. alata has 3 variants called uwi ireng, uwi ungu and uwi bangkulit. D. esculenta has 2 variants called gembili bebek and gembili terpong. The trees around Dioscorea spp obtained 21 species with the most important index is banana (Musa paradisiaca) and sengon (Albizia chinensis). The environmental factors were indicated the appropiate growth of Dioscorea spp.Â Key words: Dioscorea spp, local food stuffs and variant types